Pengembangan Media Pembelajaran Flipbook Materi Alat Ukur Dasar-dasar Teknik Mesin - Nugroho, Ananda Tri Bintang; Huda, Khoirul; Kriswanto, Kriswanto; Cahyanto, Septian Eko; Priyanto, Kaleb (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Learning in the Measuring Instruments subject in Vocational High Schools (SMK) is still dominated by traditional methods, such as lectures and the use of printed textbooks. This results in low student engagement and difficulty in understanding technical material in a practical manner. This study aims to develop and evaluate interactive flipbook-based learning media to improve student understanding of the Measuring Instruments material in the Basics of Mechanical Engineering subject. The development model used is the 4D model (Define, Design, Develop, and Disseminate), involving a validation process by material and media experts, as well as a limited trial with 40 students. The validation results showed that the material aspect achieved a feasibility score of 91.32%, while the media and design aspects achieved 94.31%. Meanwhile, student responses to the media showed an average score of 82.29%, which is categorized as very valid. This flipbook media integrates text, images, and attractive visual design, thus facilitating student understanding in a more concrete and enjoyable way.